In‐situ determination of the HfO2–Ta2O5‐temperature phase diagram up to 3000°C. Issue 8 (22nd January 2019) - McCormack, Scott J.; Tseng, Kuo‐Pin; Weber, Richard J. K.; Kapush, Denys; Ushakov, Sergey V.; Navrotsky, Alexandra; Kriven, Waltraud M.
Abstract: The previously unknown experimental HfO2 –Ta2 O5 ‐temperature phase diagram has been elucidated up to 3000°C using a quadrupole lamp furnace and conical nozzle levitator system equipped with a CO2 laser, in conjunction with synchrotron X‐ray diffraction. These in‐situ techniques allowed the determination of the following: (a) liquidus, solidus, and invariant transformation temperatures as a function of composition from thermal arrest experiments, (b) determination of equilibrium phases through testing of reversibility via in‐situ X‐ray diffraction, and (c) molar volume measurements as a function of temperature for equilibrium phases. From these, an experimental HfO2 –Ta2 O5 ‐temperature phase diagram has been constructed which is consistent with the Gibbs Phase Rule. Abstract : HfO2 –Ta2 O5 ‐Temperature phase space built based on the observed equilibrium phases from in situ X‐ray powder diffraction and the Gibbs Phase Rule.